2020
DOI: 10.3390/pharmaceutics12090884
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Almond By-Products for Intestinal Inflammation: Improvement of Physical-Chemical, Technological and Biological Characteristics of a Dried Almond Skins Extract

Abstract: Background: Almond skins are rich in bioactive compounds that undergo oxidation/degradation phenomena and are poorly soluble in water, reducing in vivo absorption and bioavailability, factors that influence the pharmacological activity of an active product. We developed a dried acetonic almond skins extract/cyclodextrin complex to improve extract solubility, dissolution rate and biological activity. Methods: A lyophilized acetonic almond skin extract was produced. To optimize complex formulation, phase solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Furthermore, the same extracts promoted the reduction of pro-inflammatory CKs levels, mostly intereleukin-1β (IL-1β) and IL-6, as well as the mediator nitric oxide (NO) levels. Such effects were in accordance with those observed for pepsin hydrolysates obtained from almond flour [67] and those provided by acetonic dried almond skin extracts from the Corrente/Tuono mixture variety on LPSinduced intestinal IEC-6 cell line, together with the inhibition of oxidative stress, via ROS levels reduction [68].…”
Section: Anti-inflammatory Activitysupporting
confidence: 89%
“…Furthermore, the same extracts promoted the reduction of pro-inflammatory CKs levels, mostly intereleukin-1β (IL-1β) and IL-6, as well as the mediator nitric oxide (NO) levels. Such effects were in accordance with those observed for pepsin hydrolysates obtained from almond flour [67] and those provided by acetonic dried almond skin extracts from the Corrente/Tuono mixture variety on LPSinduced intestinal IEC-6 cell line, together with the inhibition of oxidative stress, via ROS levels reduction [68].…”
Section: Anti-inflammatory Activitysupporting
confidence: 89%
“…The SOE sd spectra showed characteristic peaks (-OH stretching at 3275.12 cm −1 ; C-H stretching at 2932.78 cm −1 ; aromatic fingerprinting from 1868.80 cm −1 to 1829.82 cm −1 ; C=O stretching vibrations from 1772.02 cm −1 to 1670.02 cm −1 ; C=C stretching vibrations from 1636.06 cm −1 to 1507.76 cm −1 ; 1488.99 cm −1 –1472.63 cm −1 symmetric -CH 2 bending vibrations; asymmetric -CH 3 bending vibrations from 1456.95 cm −1 to 1418.70 cm −1 ; symmetric -CH3 bending vibrations from 1339.54 cm −1 to 1362.63 cm −1 ; C-C stretching from the phenyl group from 1300 cm −1 to 1450 cm −1 ; C-O stretching from 1244.07 cm −1 to 1075.17 cm −1 ) with signals ascribable to flavonoids. The region between 4000.0 cm −1 and 3000.0 cm −1 was identified as a flavonoid hydroxyl group signal; the regions at 1670.0 cm −1 and 1620.0 cm −1 were polyphenol saturation and conjugation bond signals, respectively; and 1650 cm −1 and 1600 cm −1 were identified as the characteristic aromatic signals of flavonoids [ 33 , 34 ]. Furthermore, SOE DSC showed a series of signals (from 230 °C to 270 °C) that were close together, probably ascribable to the blend of molecules belonging to the same class of polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…A statistically significant decrease in sweetness and mouthfeel notes was observed in all enriched jams, in comparison with the control jam. Despite Lauro et al [ 25 ] reported that almond skins possess “woody” and “earthy” organoleptic characteristics that can reduce the consumer’s preferences. In our case, we have not encountered this problem, since these sensory attributes are probably masked by the flavour and taste of the jam.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, clinical studies have demonstrated that a regular almond consumption can reduce the risk of several diseases in humans [ 24 ]. In part, this bioactivity can be ascribed to the phytochemicals present in the skin, particularly to the polyphenols with proven antioxidant and health-promoting activity [ 18 , 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%